Analysis of sweet potato production in the municipality of Pocinhos, Paraíba state, from 2004 to 2023 - Muniz, Janaina Iris de Azevedo Silva; Maddalena, Anddreza; Albuquerque Jr., Aldo Muniz; Sales, Lindomar Pereira da Silva; Lima, Francisco das Chagas de; Alves, Lionézia Freire; Araujo Neto, Antenor Pereira de; Barbosa, Maykon Douglas Gomes; Isidro, Renato; Abreu, Khyson Gomes; Santos, Rafaela Viturino; Andrade, Samuel Kenedi Santos; et al. (Brazilian Journal of Production Engineering, 2026)
Sweet potato (Ipomoea batatas) is a food from the Convulvulaceae family, which, due to its genetic variability, possesses diverse characteristics in terms of color, flavor, texture, shape, yield, and other attributes. It is a fundamental product in family farming in various regions of Brazil, especially in the summer, since, due to the lower need for technology during this period, there is a lower production cost. Given this scenario, this article aims to analyze the productive dynamics of sweet potato in the municipality of Pocinhos, Paraíba, from 2004 to 2023, seeking to understand the factors that influenced the behavior of this production chain and to provide subsidies for the formulation of public policies aimed at strengthening local production. The research is guided by the following guiding question: what were the trends and main indicators of sweet potato production in Pocinhos (PB) between 2004 and 2023, and what elements contributed to the variations observed during this period? The analysis of the temporal variability of sweet potato production in the municipality of Pocinhos demonstrated positive results in terms of volume produced, yield, and added value of the product, highlighting the importance of this crop for local family farming. The favorable performance observed reinforces the productive potential of the region and the growing role of sweet potatoes in the diversification of agricultural activities. Even so, it is essential to maintain investments in producer training, proper soil management, rational use of water resources, and the adoption of sustainable technological practices that guarantee the continuity of productive growth.